Philosophical-Aesthetic Peculiarities of Tamar Gabroshvili’s prose „Chrysanthemum chrysolites“ - Urdulashvili, Lali (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2019)
Tamar Gabroshvili’s prose enjoys a sharply individualistic, authorial philosophical vision. Creative works of the author are imprinted with this spiritual handwriting. That is why she is so distinctive with her specific voice in the modern literary space. Her philosophical observations show her artistic-aesthetic thought. The concept of Tamar Gabroshvili’s literary work is the world and a human. In the writer’s philosophical and aesthetic thought, a human equals a divine instrument created by God, to whom God gives a continuous spiritual flow by bestowing the art of singing and speaking. According to the author, if it were not so, man could not be human. It would be like a trumpet, a lifeless instrument. A man aspiring to desolation, loneliness, and self-loathing reminds the writer of that beautiful poisonous flower that no one can touch, neither animal nor human. In his conclusion, humanity is much more than being alone with yourself, asceticism. For God, acceptable is the person who is in the community and serves him (we remember Ilia’s “Hermit”), otherwise, a person is doomed to die. Humanity means being everywhere and with everyone like the sun. Only then can God’s beloved creatures radiate warmth, light like the sun, and warm those around them. Anyone who resembles God can do this. All of us are born with the Lord’s mercies. This treasure should be uncovered and well cared for. Everyone has their ‘inner world’ for their benefit and that of others. The heart has special significance in the writer’s artistic thought. He considers the human heart to be an integral part of one universal heart, which blocks good thoughts in the human mind and does not give them freedom. She calls this heart a nurturer that brings a person to equilibrium. The writer’s creative belief directs the reader’s thinking to the truth that man, born like the Lord, must cross the bridge from the C-CW to the C-C-A-C.